1988
DOI: 10.1159/000184864
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vascular Calcinosis Risk Factors in Patients on Chronic Hemodialysis: Lack of Influence of Calcium Carbonate

Abstract: Linear calcifications of the abdominal aorta and of the iliac and femoral arteries were measured yearly for 3 years on X rays of 24 patients on chronic hemodialysis taking variable amounts of calcium carbonate and Al(OH)3 but no pharmacological doses of vitamin D or lα-hydroxylated vitamin D derivatives. The speed of their extension appeared exponential and covariant with the male sex, age only for men and, independently of these two factors, with diastolic blood pressure and blood triglycerides. Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Since then, numerous, though not all, studies have shown a correlation between high serum phosphate and the incidence or rate of progression of large artery VC [13, 16, 39, 40, 41], of CUA [23, 26, 29, 30], and of CAC [5]. Hyperphosphataemia has recently been shown to be an independent predictor of death amongst haemodialysis patients [42, 43].…”
Section: Causes Of and Risk Factors For Vc In Esrdmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, numerous, though not all, studies have shown a correlation between high serum phosphate and the incidence or rate of progression of large artery VC [13, 16, 39, 40, 41], of CUA [23, 26, 29, 30], and of CAC [5]. Hyperphosphataemia has recently been shown to be an independent predictor of death amongst haemodialysis patients [42, 43].…”
Section: Causes Of and Risk Factors For Vc In Esrdmentioning
confidence: 99%
“…Progression of VC was related to hypertriglyceridaemia in a longitudinal study in France [40]. As discussed above, the beneficial effects of sevelamer on CAC [7]may have been due to its cholesterol-lowering effects.…”
Section: Causes Of and Risk Factors For Vc In Esrdmentioning
confidence: 99%
“…Hyperphosphataemia accompanying chronic renal failure is a major contributor to the development of renal osteodystrophy [1, 2, 3, 4]and soft-tissue calcification [5, 6, 7]. Accelerated vascular calcifications (coronary and valvular) are common in chronic dialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…To determine cardiovascular morphological changes in ESRD patients, echocardiography, CT tomography and radiography have been used in many studies. Many investigations regard arterial calcification as a representative vascular alteration in ESRD patients [6, 7, 8, 9, 10]. However, it is difficult to thoroughly evaluate cardiovascular changes in living patients.…”
Section: Introductionmentioning
confidence: 99%